Remarkable Response of Metastatic Gallbladder Carcinoma to Apatinib After Failed Multiline Chemotherapies: A Case Report and Literature Review - Zhang, Mengxi; Zhang, Pengfei; Zhou, Kexun; Li, Qiu (Frontiers in Oncology, 2019)
Gallbladder carcinoma (GBC) is a relatively rare and aggressive malignant tumor, with a poor prognosis. Systematic review of current clinical studies illustrates an extreme paucity of the second-line therapeutic options following the failure of standard-of-care cisplatin-gemcitabine chemotherapy. The efficacy of apatinib, an oral, highly potent and selective inhibitor of VEGFR-2 tyrosine kinase, for refractory advanced GBC has not yet been clarified. Herein, we report a case of advanced GBC that presented a durable partial response to apatinib as monotherapy after the failure of multiline chemotherapies including S-1 monotherapy, capecitabine monotherapy, gemcitabine plus capecitabine and irinotecan plus oxaliplatin. The patient achieved an efficacy of partial response within two months. By September 23, 2019, the duration of treatment had extended for almost one year with a satisfactory quality of life, and the administration of apatinib was continued. Dose reduction of apatinib occurred at week four due to grade 2 hypertension and hand-foot skin reaction (HFSR). No fatigue, proteinuria, mucositis or thrombocytopenia occurred. To the best of our knowledge, this is the first case of a successful use of apatinib monotherapy for heavily pretreated GBC. Further prospective studies are warranted to confirm the efficacy and safety of apatinib in GBC.